2022
DOI: 10.1109/jphot.2022.3169711
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Metasurface Inspired Directional Multi-Port Luneburg Lens as a Medium for 5G Wireless Power Transfer—A Design Methodology

Abstract: In this paper, a novel dielectric metasurface-inspired multi-beam directional Luneburg lens is proposed as a wireless power transfer medium at 5G mm-wave band. The lens is constructed using dielectric-based unit cells made up of a glide symmetric approach. It is connected with a set of microwave detector integrated multi-port tapered rectangular feeds to convert the received RF energy from different directions to DC power across a combined load. The proposed structure can be a potential candidate to harvest am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The proof is easily extendable to the 2D case, i.e., to G matrices with elements g ′ mn,pq = (−1) (m−p) (−1) (n−q) . Using this lemma and previously proved property (71) it is easily shown that A (glide) = G ⊙ A (the definition of A is given in (17) and ( 41)). The eigendecomposition on this result gives…”
Section: Connection Between Eigenvector Matrices For Nominal and Glid...mentioning
confidence: 79%
See 1 more Smart Citation
“…The proof is easily extendable to the 2D case, i.e., to G matrices with elements g ′ mn,pq = (−1) (m−p) (−1) (n−q) . Using this lemma and previously proved property (71) it is easily shown that A (glide) = G ⊙ A (the definition of A is given in (17) and ( 41)). The eigendecomposition on this result gives…”
Section: Connection Between Eigenvector Matrices For Nominal and Glid...mentioning
confidence: 79%
“…1, became popular over the past couple of years for the realization of planar gradient index (GRIN) lens antennas, mostly because the dispersion properties of glide-symmetric structures enables the realization of frequency wideband lenses [9]. So far, such planar GRIN lenses for microwave frequencies have been proposed with fully metallic [10]- [13], printed circuit board [14]- [16], and fully dielectric 3D printed unit cells embedded in PPW [7], [8], [17]. In this paper we consider the latter solution, i.e., the loading GRIN media can be manufactured by commercially available additive manufacturing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial concept, several configurations using metamaterials have been presented (Ranaweera et al , 2019; Zhang et al , 2019; Bui et al , 2020; Rong et al , 2021; Lan et al , 2022), while instructive WPT realisations have, also, encompassed other emerging scientific domains (Li et al , 2018; Das et al , 2019; Gong et al , 2022; Tian et al , 2022; Wang et al , 2022). To this aim, the split-ring resonators (SRRs) are deemed the most commonly used elements, which conduct field amplification by modifying the electric and magnetic field distribution, because of their negative constitutive parameters (Gámez Rodríguez et al , 2016; Corrêa et al , 2019; Leumüller et al , 2022; Majumder et al , 2022). Hence, properly tuned SRR loops lead to highly efficient devices, whose size is much smaller, compared to typical ones and can be coupled with external fields in free space, allowing fairly instructive implementations (Brizi et al , 2020; Pokharel et al , 2021; Lu et al , 2021; Wang et al , 2022; Wei et al , 2022).…”
Section: Introductionmentioning
confidence: 99%